Analyze Factors that Affect Member Engagement in Unit Kesenian Minangkabau Institut Teknologi Bandung (Journal of Business and Management, 2022)
A goal can be reached in an organization if a group of people in the organization feel like they belong to each other. The importance of member engagement has become a concern by one of student organization, Unit Kesenian Minangkabau Institut Teknologi Bandung. This study aims to identify factors that influenced member engagement in UKM-ITB and find out the strategy that should be taken by UKMITB to improve its member engagement. Qualitative research method is used in this study. Triangulation data source is used to validate data. Data collection was carried out online through semi-structured interviews with 10 informants that consist of active members of UKM-ITB batch of 2017 to 2019. Content analysis is used by using coding for data analysis. The results of this study are team and co-worker relationships are significant factors in influencing member engagement followed by leadership, internal communication, organizational culture, and responsibility. The strategy that should be taken by UKM-ITB to improve its member engagement are increasing events that is directed for member bounding, holding events based on member's wishes, changing the recruitment system, changing the forum system, and improving board of director’s professionality and commitment.Keyword: Member Engagement, Non-profit Organization, Student Organization